Muatan Mendasar Metafisika dalam Perspektif Al-Ghazali dan Ibnu Sina - Yogi Fery Hidayat (UPT Publikasi Ilmiah, 2025)
This research aims to compare the metaphysical views of two great Islamic figures, Al-Ghazali and Ibn Sina, with a focus on the concepts of reality, entities, and the essence of existence. The method used is a literature study by collecting data from classic texts written by both figures. The data is analyzed by comparing the differences and similarities of their views on the metaphysical concepts under study. The results of the research indicate that Al-Ghazali and Ibn Sina have some significant differences regarding reality, entities, and the essence of existence, namely (1) Al-Ghazali claims that reality can only be understood through direct experience, while Ibn Sina believes that reality can be achieved through both experience and rational thinking. (2) Al-Ghazali believes that the essence of existence is eternal, while Ibn Sina considers it dynamic and changeable. (3) Al-Ghazali regards individual entities as something real, whereas Ibn Sina states that individual entities are only a part of a larger reality. (4) Al-Ghazali believes that reason must be adjusted to spiritual experience, while Ibn Sina considers them mutually supportive. (5) Al-Ghazali emphasizes faith and spiritual experience, while Ibn Sina regards religion as a tool to strengthen human intelligence in seeking the truth. Nevertheless, the research also found similarities between them regarding reality, entities, and the essence of existence, namely (1) Both agree that reality, entities, and the essence of existence are interrelated and cannot be understood separately. (2) The existence and essence of an entity depend on the properties inherent in the entity itself. (3) There is a close relationship between reality, entities, and the essence of existence with religion and spirituality. (4) Allah is the source of the existence and essence of all entities in reality.